The Change My Great American, Postindustrial, Midlife Crisis Tour - Soderlind, Lori (The University of Wisconsin Press, 2020)
In the throes of a classic midlife crisis, Lori Soderlind takes a sabbatical from her community college job as a journalism professor. She sets out to travel across America's rusting heart with her fourteen-year-old dog, Colby, and a used camping trailer. Making pit stops in places like Buffalo and Rockford, she explores a deeply conflicted country going through its own crises and transformations. Even as she struggles with her own impulses, she finds life and resilience among the seemingly forlorn, abandoned artifacts of former industrial glory. With humanity and humor, Soderlind's journey introduces quirky folks along the way, including Swannie Jim of Silo City and his fawn pit bull, Champ. She attempts to channel muckraking journalist Ida M. Tarbell and celebrates complicated characters, including Robert De Niro's heartbroken veteran in The Deer Hunter. Ultimately a romance-of Soderlind's love for America, her dog, the long-term partner she left behind, and the childhood crush she remembers with a big, aching pang-The Change offers daring and often hilarious insights into loss and acceptance, especially when it takes a while to get there.